Crafting and executing strategy : the quest for competitive advantage : concepts and cases - Thompson, Arthur A., 1940-; Strickland, A. J. (Alonzo J.); Gamble, John (John E.) (Boston : McGraw-Hill/Irwin, 2010)
Presenting the most recent developments in research and strategy, this text applies these theories and illustrates their implementation in business cases.
Concepts and techniques for crafting and executing strategy -- Cases in crafting and executing strategy.
Includes bibliographical references and index.
Keywords: Strategic planning; Strategic planning -- Case studies; Business planning